Leading without authority why you don?t need to be in charge to inspire others and make change happen - Ferrazzi, Keith (London Penguin Business, 2020)
The #1 New York Times bestselling author Keith Ferrazzi argues that in times like these the ability to lead without authority is the essential workplace competency. Leading Without Authority reveals the secret to getting those around you to collaborate and cooperate to reach their full potential, whatever your title. The answer involves a shift in mindset that Ferrazzi calls co-elevation - working to elevate those around us. And you don't have to have formal authority, or direct reports, to utilize the co-elevation process. In fact, you can take initial steps forward without the other person even being aware of your efforts.
Includes bibliographical references and index.
Keywords: BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Personal Success; SELF-HELP / Personal Growth / Success